Determinants of Profitability: A Study on Manufacturing Companies Listed on the Dhaka Stock Exchange - Hossain, Tarik (Asian Economic and Financial Review, 2020)
This study aim to establish the crucial determinants of the profitability of manufacturing companies listed on the Dhaka Stock Exchange (DSE). Data were collected from different manufacturing companies listed on the DSE from 2014 to 2019. Pearson’s correlation and ordinary least squares regression models were used to establish the relationship among profitability and different determinants of profitability such as liquidity, leverage, sales growth, management efficiency, capital intensity, firm size, working capital, annual inflation and GDP growth. The regression analysis results showed that liquidity and leverage have a statistically significant negative impact on profitability. On the other hand, managerial efficiency, sales growth and capital intensity have a statistically significant positive impact on profitability. The study also found that firm size, working capital, annual inflation and GDP growth have no significant impact on profitability. The study concludes that liquidity, leverage, managerial efficiency, sales growth and capital intensity are the strong determinants of profitability of the manufacturing companies. This paper consists of two major parts, the theoretical part and the empirical part. In the theoretical part, a brief discussion has been given about the different variables of profitability. The empirical part is based on a survey conducted on 34 manufacturing companies on the Dhaka Stock Exchange. Finally, some recommendations are made for the manufacturing companies regarding determinants of profitability. The policy implication is that potential investors should consider these determinants before making investment decisions in manufacturing companies.